The failure of regional refugee protection and responsibility sharing: Policy neglect in the EU and ASEAN. (June 2019) - Tubakovic, Tamara
The concurrent refugee crises affecting the European Union (EU) and the Association of South East Asian Nations (ASEAN) brought to the fore long-standing issues regarding regional cooperation on refugee protection and responsibility sharing. This article argues that these crises are a culmination of years of policy neglect. By comparing the EU and ASEAN, this article demonstrates the weaknesses of regional bodies in responding to refugee challenges, regardless of the level of institutionalization of refugee norms and practices. In both instances, procedural norms privileging member state interests and consensus have hindered the development of durable regional refugee policies.